Job characteristics affecting employees' job involvement in fast food industry - Nurul Salwana, Mohamad Kamal (2013)
Employees' job involvement has been found decreasing over the change of time. Therefore, the issue relates with employees‟ job involvement is getting concern from other researchers due to lack of previous studies done for it. The purpose of this research is to investigate the factor of job characteristics model (JCM) (skill variety, task identity, task significance, autonomy and feedback of the job) that affects KFC fast food restaurant employee job involvement in Malaysia. In this research project, quantitative method has been used as method of questionnaire in order to collect data from respondents. Questionnaires were administrated in KFC fast food restaurant in Rawang Branch, Selangor. Besides that, questionnaire also was distributed by using closed-ended question method. The pilot test has been conducted to analyses the reliability of the question before actual study. This research used Pearson correlation coefficient to analyses 86 responses from the questionnaire obtained. Moreover, multiple regressions revealed that the five sources of factors (skill variety, task identity, task significance, autonomy and feedback of the job) had significant positive relationship with employee job involvement in Malaysia. Furthermore, this research also will explore which factor in JCM will affect employees‟ job involvement in KFC fast food industry in Rawang, Selangor.